Price Advertising by Manufacturers and Dealers - Xu, Linli; Wilbur, Kenneth C.; Siddarth, S.; Silva-Risso, Jorge M. (Management Science, 2014)
The central prediction of the current paper is that manufacturer price advertising may be a less effective tool for influencing demand than retailer price advertising. We manipulate the source of a price advertisement in an experiment run on a sample of pickup truck owners. Manufacturer price advertising leads to lower indicators of potential demand than dealer price advertising, even among consumers who are experienced with the brand. An econometric analysis of pickup truck sales, price, and advertising data shows that this effect is large enough to detect in market data. Manufacturer and dealer price advertising both increase the demand intercept and the responsiveness of demand to price, but the effects of dealer price advertising are larger. Although dealer price advertising is more effective than manufacturer price advertising, manufacturer price advertising may still be useful to reduce channel conflict. This paper was accepted by Pradeep Chintagunta, marketing.